Helicobacter pylori infection and assessment of related factors among Healthy Residents and students in Msallata city (Comprehensive Journal of Science, 2025)
Helicobacter pylori is one of the most common chronic bacterial infections globally, causing a widerange of illnesses including gastritis, peptic ulcers, gastric carcinoma, and mucosa-associatedlymphoid tissue (MALT) lymphoma